Effects of temperature on sound production in the painted goby Pomatoschistus pictus - Vicente, Joana R. (2015)
The painted goby Pomatoschistus pictus emits courtship sounds (drums) that are important in reproductive outcome. The effect of temperature (14–22 °C) on courtship drum features was characterised. Pulse period (or rate) was linearly related with temperature (R2 = 0.83) presenting a Q10 of 2.13. Pulse period decreased by 1.95 ms per 1 °C and varied from 34 ms to 18.6 ms within the studied temperature range. Sound duration changed concomitantly from 1128 ms to 658 ms. Changes in sound duration were due to pulse period rather than pulse number, since the latter was not affected by temperature. Pulse duration was similarly affected by temperature, decreasing by 0.3 ms per 1 °C (R2 = 0.51, Q10 = 1.45) and changing from 10.0 ms at 14 °C to 7.5 ms at 22 °C. Drum emission rate, sound amplitude, fatigue and dominant frequency were also not related to temperature. The temperature effect on pulse rate likely reflects temperature-dependence of the vocal central pattern generator as observed in other animals. In contrast, shorter pulse durations likely result from temperature effects at the peripheral level of the vocal system, as muscle twitches typically shorten with rising temperatures. Because pulse rate is likely important in mate choice and conspecific recognition in fish, including P. pictus, future studies are needed to understand if temperature-related changes in pulse rate are coupled with changes in mate preference as found in insects and anurans.